Control and planning in the development of female gymnasts` motor skills - Buftea, V. (The European Proceedings of Social & Behavioural Sciences EpSBS, 2018)
The aim of this paper is to improve the monitoring of complete training through effective use of control and planning in the development of female gymnasts` motor skills within an Olympic training cycle. An experimental study was made to this end in all micro-, mezzo- and macro-cycles of the four-year training cycle. The study revealed the increase of complex motricity when achieving high sports performances. During this research, 14 parameters were tested to determine the gymnasts` motor training while evaluating their progression too. The comparative analysis results showed significant differences between the experimental group subjects. These results were compared with each other during macro-cycles of the 2nd, 3rd and 4th training year. There were also highlighted significant differences between the results obtained by the experimental group subjects who carried out their activity according to the developed models and the control and planning system strategy and the results obtained by the subjects in the control group where these developments were not applied. The analysis of performances obtained by the two groups monitored during their motor training highlighted significant results of the experimental group, with a probability of P < 0.05 as for the calculation of the difference between statistical indicators tested in the first macro-cycle and data obtained in the second macro-cycle of the Olympic cycle. The application of the control and planning system for motor skill development provided useful information for the safe and effective monitoring of the full training of gymnasts under research.